Aspek-aspek Resiliensi Dakam Syair Hamasah Karya Mutanabbi - Rohmat (HUMANISTIKA : Jurnal Keislaman, 2020)
Human life in the world is inseparable from the various life problems that take turns. People with high levels of resilience will be able to get through all the problems of their lives safely and successfully. However, for someone who has a low level of resilience will consider all the problems faced as a disaster that increasingly makes it sink and fall. On one side of the problem of life is an exercise that will strengthen humans in reaching a higher degree of life. Resilience is the ability to adapt to life's suffering that befalls and then there are efforts to raise and overcome it. This paper contains an analysis of several poems by Mutanabbi, he was a medieval Arabic poet who composed many poems with the theme of hamasah which contained elements of resilience. The method used by the author is to use content analysis with structural analysis.